Penerapan Teori Belajar Behavioristik B. F. Skinner dalam Pembelajaran : Studi Analisis Terhadap Artikel Jurnal Terindeks Sinta Tahun 2014 - 2020 - Kiki Melita Andriani; Maemonah; Rz. Ricky Satria Wiranata (STAI Terpadu Yogyakarta, 2022)
This research is motivated by the fact that the theories that have developed so far usually experience a cycle of change from time to time, including the theory of behaviorism. This theory is interesting to measure, observe, analyze, and test objectively in a scientific framework. The problem in this research is how the role and development of the application of behavioristic learning theory in learning. This research is qualitative. The approach in this study is a critical analysis of the behavioristic learning theory of B.F. Skinner who developed in the world of education. The source of data in this study is library research through critical analysis of sinta indexed journal articles in 2014-2020. The results of the research analysis concluded that the thinking of B.F. Skinner is in line with Al-Gazali's thoughts and Abdullah Nasih 'Ulum's thoughts on educational thinking, namely changes in student behavior will be influenced by the learning environment, one of which is the educator, then a child will become a good person if the educator has a good personality too